الفرائد المنتظمة والفوائد المحكمة فيما يقال في ابتداء تدريس الحديث الشريف تتعلق بالبخاري وبأول ما له من ترجمة للإمام المحدث محمد بن أحمد بن علي بن أبي بكر الغيطي "ت 982 هـ.": دراسة وتحقيق - الغيطي، محمد بن أحمد بن علي بن أبي بكر، ت. 982 هـ. Alghaiti, Mohammed Bin Ahmed Bin Ali Bin Abi Bakr; المطيري، محمد الحميدي حمود (جامعة الزرقاء - عمادة البحث العلمي, 2021)
هذا البحث عبارة عن تحقيق رسالة حديثية للعلامة محمد بن أحمد بن علي بن أبي بكر الغيطي المتوفي (982 ه)، يمهد فيها الشيخ لتدريس صحيح البخاري؛ من خلال المرور على ما يتحتم العلم به قبل الشروع في الصحيح، وقد امتازت الرسالة بأسلوب حديثي واضح، اقتصر المؤلف فيها على ذكر المسائل الحديثية المتعلقة بكتاب صحيح البخاري على سبيل الاختصار، وقد حققت الرسالة معتمدا على نسختين، كتبتا بخط واضح لم تتعذر قراءتها إلا في مواطن قليلة، ابتدأت تحقيقها بمقدمة تحدثت فيها عن المؤلف، ثم ترجمت له ترجمة وافية، ذكرت فيها كل ما أمكنني الوقوف عليه من أحواله. وأما النص المحقق فقد خدمته بضبطه، وشرح مصطلحاته، وتوثيق نقوله، وقمت بتخريج مختصر للأحاديث الواردة في الرسالة.
This paper is an edited and revised version of a handwritten manuscript in Hadith literature، written by a well known and distinguished scholar of his era namely Muhammad Ibn Ahmad Ibn 'Ali Ibn Abi Bakr Al-Ghaiti (982H). He wrote this manuscript in a size of booklet for his students as a brief introduction before he begins teaching them Sahih Al-Bukhari by explaining some of the crucial and important informations concerning Sahih Al-Bukhari before they advance in learning it. This introductional booklet is distinguished from others by its remarkable method of academically summarizing Hadith discourses related to Sahih Al-Bukhari. This work is edited and revised according to two original manuscripts which can be read with ease except for some places. This work begins with a lengthy introduction of the writer's biography by mentioning all the aspects found. As for the editing work, a great focus is given to the rewriting of the manuscript accurately, explaining its technical terms and authenticating the information mentioned therein by stating their original sources. Special attention is also given to all the Hadith mentioned in the introduction booklet by mentioning their sources and status thoroughly.
Keywords: الأحاديث النبوية -- تدريس الأحاديث النبوية -- كتب الحديث -- كتاب صحيح البخاري -- تحقيق المخطوطات -- رسالة الفرائد المنتظمة والفوائد المحكمة -- الغيطي، محمد بن أحمد بن علي بن أبي بكر، ت. 982 هـ